On the question of a research school boundaries(a problem to discuss) - M. N. Kolesnikova; E. V. Bakhtina (Библиосфера)
The problem of determining scientific school borders on example of the composition and structure of the Le- ningrad library scientist V. F. Saharov scientific school is considered.